2016
DOI: 10.1080/08897077.2015.1129528
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on An Opioid Overdose Education and Naloxone Distribution Program in the U.S. Department of Veterans Affairs

Abstract: OEND training was generally well received among study participants, including those with no indication for a naloxone kit. Patients described a need for OEND and believed it could save lives. Patient feedback on OEND training benefits, concerns, opinions, and suggestions provides important insights to inform future OEND training programs both within VA and in other health care settings. Training is critical to maximizing the potential for OEND to save lives, and this study includes specific suggestions for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…The key elements of these programs were the education of people who use opioids about how to reduce their overdose risk and equipping them with naloxone, the antidote to an opioid overdose, so that they could rescue each other. Since then, these programs have expanded substantially in the United States and Canada to become a leading public health intervention for the prevention of overdose mortality (Oluwajenyo Banjo et al, 2014; Wheeler et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key elements of these programs were the education of people who use opioids about how to reduce their overdose risk and equipping them with naloxone, the antidote to an opioid overdose, so that they could rescue each other. Since then, these programs have expanded substantially in the United States and Canada to become a leading public health intervention for the prevention of overdose mortality (Oluwajenyo Banjo et al, 2014; Wheeler et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…These findings contributed to initiation of a national overdose education and naloxone distribution program through the Department of Veterans Affairs (Oliva et al, 2016) and informed the CDC chronic pain guidelines that encourage naloxone co-prescribing to patients on prescription opioids long-term for non-cancer pain (Dowell, Haegerich, & Chou, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…10 Large health systems have now begun to promote naloxone Bco-prescribingf or patients prescribed opioids for CNCP. [11][12][13] Prior research suggests that providers may be reluctant to prescribe naloxone to patients with CNCP because of several logistical and attitudinal barriers.…”
Section: Introductionmentioning
confidence: 99%
“…9 There is therefore a role and an opportunity to consider naloxone supply in a range of populations at risk of opioid overdose. 10 The feasibility of a take-home naloxone supply has been demonstrated in Sydney with 30 successful overdose reversals reported in a trial of 83 participants. 11 This is in addition to numerous international studies that have shown that supplying naloxone for layperson administration is safe, feasible and cost-effective.…”
Section: Articlementioning
confidence: 99%